Proton density water fraction as a reproducible MR‐based measurement of breast density. Issue 4 (14th November 2021) - Henze Bancroft, Leah C.; Strigel, Roberta M.; Macdonald, Erin B.; Longhurst, Colin; Johnson, Jacob; Hernando, Diego; Reeder, Scott B.
Abstract : Purpose: To introduce proton density water fraction (PDWF) as a confounder‐corrected (CC) MR‐based biomarker of mammographic breast density, a known risk factor for breast cancer. Methods: Chemical shift encoded (CSE) MR images were acquired using a low flip angle to provide proton density contrast from multiple echo times. Fat and water images, corrected for known biases, were produced by a six‐echo CC CSE‐MRI algorithm. Fibroglandular tissue (FGT) volume was calculated from whole‐breast segmented PDWF maps at 1.5T and 3T. The method was evaluated in (1) a physical fat‐water phantom and (2) normal volunteers. Results from two‐ and three‐echo CSE‐MRI methods were included for comparison. Results: Six‐echo CC‐CSE‐MRI produced unbiased estimates of the total water volume in the phantom (mean bias 3.3%) and was reproducible across protocol changes (repeatability coefficient [RC] = 14.8 cm 3 and 13.97 cm 3 at 1.5T and 3.0T, respectively) and field strengths (RC = 51.7 cm 3 ) in volunteers, while the two‐ and three‐echo CSE‐MRI approaches produced biased results in phantoms (mean bias 30.7% and 10.4%) that was less reproducible across field strengths in volunteers (RC = 82.3 cm 3 and 126.3 cm 3 ). Significant differences in measured FGT volume were found between the six‐echo CC‐CSE‐MRI and the two‐ and three‐echo CSE‐MRI approaches ( p = 0.002 and p = 0.001, respectively). Conclusion: The use of six‐echo CC‐CSE‐MRI to create unbiased PDWF maps that reproducibly quantify FGT in the breast is demonstrated. Further studies are needed to correlate this quantitative MR biomarker for breast density with mammography and overall risk for breast cancer.